Behavioral Finance and Investment Decision-Making Among Young Investors - Klemens Mere (Yayasan Riset dan Pengembangan Intelektual, 2024)
Behavioral finance combines insights from psychology and economics to explain how investors’ cognitive biases, emotions, and social influences affect their financial decisions. The purpose of this study is to analyze Behavioral Finance and Investment Decision-Making Among Young Investors. This study employs a qualitative approach using the literature review method to investigate how principles of behavioral finance influence investment decision-making among young investors. A literature review is appropriate for synthesizing theoretical concepts, empirical findings, and methodological trends from previously published academic sources. This literature review concludes that behavioral finance has a significant and measurable impact on the investment decisions of young investors. Unlike traditional financial theories that assume rational behavior, behavioral finance recognizes the psychological and emotional influences that drive real-world financial decisions.